RELATIONSHIP BETWEEN PRODUCT DIVERSIFICATION AND UNDERWRITING PERFORMANCE IN UK PROPERTY-LIABILITY INSURANCE MARKET - Nghiem, Hien (2012)
This paper aims to investigate the relationship between product diversification and underwriting performance. To do this, we use panel data analysis on a long panel data set of UK property-liability insurance market for period from 1985-2010. Our analysis encompasses two stages. Firstly, we examine the effect of product diversification on performance using the whole panel data. The results indicate that diversification has positive relationship with performance, which means that specialized insurers perform better than diversified insurers. Secondly, we apply the same analysis but to two sub-samples using aggregated data from soft and hard market phases of the underwriting cycles. Under this further investigation, diversification appears to support insurers’ performance during hard market phase, while the negative impact remains during soft market phase.